1999
DOI: 10.1023/a:1008347829017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of patients with unresectable colorectal cancer liver metastases following infusional chemotherapy with 5-fluorouracil, leucovorin, oxaliplatin and surgery

Abstract: This new strategy of combining effective chemotherapy with surgery apparently altered the natural history of unresectable colorectal cancer metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
212
0
27

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(246 citation statements)
references
References 34 publications
5
212
0
27
Order By: Relevance
“…Neoadjuvant chemotherapy prior to surgery can downstage previously unresectable hepatic metastases in up to 38% of patients and ease the resection in those already resectable [11][12][13]. Despite improved selection of patients, outcome remains the same with an overall 5-year survival similar in patients with clinically resectable metastatic disease with and without neoadjuvant chemotherapy prior to resection (52% vs. 38% respectively, P ¼ 0.35) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy prior to surgery can downstage previously unresectable hepatic metastases in up to 38% of patients and ease the resection in those already resectable [11][12][13]. Despite improved selection of patients, outcome remains the same with an overall 5-year survival similar in patients with clinically resectable metastatic disease with and without neoadjuvant chemotherapy prior to resection (52% vs. 38% respectively, P ¼ 0.35) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Giacchetti et al (1999) reported that 77 out of 151 (51%) patients had surgery with curative intent following neoadjuvant treatment with 5-FU/FA/oxaliplatin. Complete resection was achieved in 58 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the remainder, the hepatic lesion is either ill sited, too large or multinodular, and therefore deemed to be unresectable. In a proof-of-principle retrospective study, evaluating a chronomodulated schedule of 5-FU/FA and oxaliplatin, Giacchetti et al (1999) demonstrated that first-line cytotoxic chemotherapy had downsized a significant fraction of unresectable disease to operability. Specifically, following the treatment of 151 patients with liver-only, previously inoperable metastatic disease, 77 were subsequently resected with curative intent.…”
Section: Hepatic Resectionmentioning
confidence: 99%